Interactive effects of temperature, phosphorus and forest floor structure on enchytraeidae communities (Annelida, Clitellata) - Jingxuan Olivia Chen; Rebecca Rodewald; Natalija Vasilevska; André Junggebauer; Mark Maraun; Bastian Heimburger; Stefan Scheu; Ina Schaefer (Soil Biology and Biochemistry, 2026)

Convergent evolution revealed by paraphyly and polyphyly of many taxa of oribatid mites: A molecular approach - Peter Cordes; Xue Pan; Maka Murvanidze; Anna Seniczak; Stefan Scheu; Ina Schaefer; Mark Maraun; Bastian Heimburger (Experimental and Applied Acarology, 2024)
A reliable phylogeny is crucial for understanding the evolution and radiation of animal taxa. Phylogenies based on morphological data may be misleading due to frequent convergent evolution of traits—a problem from which molecular phylogenies suffer less. This may be particularly relevant in oribatid mites, an ancient soil animal taxon with more than 11,000 species, where the classification of species into high-ranking taxa such as superfamilies is equivocal. Here, we present a molecular phylogeny of 317 oribatid, 4 astigmatid and 17 endeostigmatid mite species/taxa based on 18S rDNA sequences. We aimed at testing the validity of the 41 superfamilies of oribatid mites recognized by Norton and Behan-Pelletier (in Krantz and Walter, A manual of Acarology, 3rd ed., Texas Technical University Press, Lubbock, 2009). The results indicate that 17 of the 41 oribatid mite superfamilies are monophyletic but that 18 superfamilies are paraphyletic or polyphyletic (5 superfamilies were only included with one species and Microzetoidea were not included). Our findings point to the importance of convergent evolution in polyphyletic oribatid mite taxa. Convergent evolution and the old age of mites likely resulted in a mosaic-like distribution of morphological characters impeding phylogenetic reconstructions based on morphology, calling for molecular approaches to improve oribatid mite systematics.

Genomic evidence for the widespread presence of GH45 cellulases among soil invertebrates - Hannah Muelbaier; Freya Arthen; Gemma Collins; Thomas Hickler; Karin Hohberg; Ricarda Lehmitz; Yannick Pauchet; Markus Pfenninger; Anton Potapov; Juliane Romahn; Ina Schaefer; Stefan Scheu; et al. (Molecular Ecology, 2024)
Lignocellulose is a major component of vascular plant biomass. Its decomposition is crucial for the terrestrial carbon cycle. Microorganisms are considered primary decomposers, but evidence increases that some invertebrates may also decompose lignocellulose. We investigated the taxonomic distribution and evolutionary origins of GH45 hydrolases, important enzymes for the decomposition of cellulose and hemicellulose, in a collection of soil invertebrate genomes. We found that these genes are common in springtails and oribatid mites. Phylogenetic analysis revealed that cellulase genes were acquired early in the evolutionary history of these groups. Domain architectures and predicted 3D enzyme structures indicate that these cellulases are functional. Patterns of presence and absence of these genes across different lineages prompt further investigation into their evolutionary and ecological benefits. The ubiquity of cellulase genes suggests that soil invertebrates may play a role in lignocellulose decomposition, independently or in synergy with microorganisms. Understanding the ecological and evolutionary implications might be crucial for understanding soil food webs and the carbon cycle.

Assessing extraradical mycelium of mycorrhizal fungi in tropical forests using armored in-growth mesh bags - Andrey G. Zuev; Ivan V. Gruzdev; Anton M. Potapov; Ina Schaefer; Stefan Scheu; Alexei V. Tiunov; Nguyen Van Thinh; Anna I. Zueva (Pedobiologia, 2024)

Differential changes in body size and stoichiometry in genetic lineages of the earthworm Eisenia nordenskioldi with elevation - Tingting Xiao; Bing Zhang; Huifeng Zhao; Zhijing Xie; Yufeng Zhang; Donghui Wu; Ting-Wen Chen; Stefan Scheu; Ina Schaefer (Soil Biology and Biochemistry, 2024)

Population structure and genetic variance among local populations of a non-native earthworm species in Minnesota, USA - Bastian Heimburger; Andreas Klein; Alexander Roth; Stefan Scheu; Nico Eisenhauer; Ina Schaefer (Biological Invasions, 2023)
A variety of human activities have been identified as driving factors for the release and spread of invasive earthworm species in North America. Population genetic markers can help to identify locally relevant anthropogenic vectors and provide insights into the processes of population dispersal and establishment. We sampled the invasive European earthworm species Lumbricus terrestris at nine sites and several bait shops within the metropolitan area of Minneapolis-St. Paul in Minnesota, USA. We used microsatellite markers to infer genetic diversity and population structure, and 16S rDNA to address multiple introduction events, including bait dumping, which is a common source of L. terrestris introductions into the wild. Our results indicate multiple introductions but not from current bait dumping. Overall, genetic structure was low and earthworms > 5,000 m apart were genetically differentiated, except for one sampling location, indicating jump-dispersal followed by population establishment. Further, earthworms at one location north of Minneapolis established from one or few founder individuals, suggesting that earthworm invasions are ongoing. We therefore encourage further monitoring of earthworm populations using molecular markers, in order to disentangle the different human-related vectors contributing to the spread of earthworms and their establishment, which is essential to develop adequate management strategies.

New perspectives on soil animal trophic ecology through the lens of C and N stable isotope ratios of oribatid mites - Mark Maraun; Tanja Thomas; Elisabeth Fast; Nico Treibert; Tancredi Caruso; Ina Schaefer; Jing-Zhong Lu; Stefan Scheu (Soil Biology and Biochemistry, 2023)

Dispersal patterns of oribatid mites across habitats and seasons - Peter Hans Cordes; Mark Maraun; Ina Schaefer (Experimental and Applied Acarology, 2022)
Oribatid mites are tiny arthropods that are common in all soils of the world; however, they also occur in microhabitats above the soil such as lichens, mosses, on the bark of trees and in suspended soils. For understanding oribatid mite community structure, it is important to know whether they are dispersal limited. The aim of this study was to investigate the importance of oribatid mite dispersal using Malaise traps to exclude sole passive wind-dispersal. Oribatid mite communities were collected over a 3-year period from five habitat types (coniferous forests, deciduous forests, mixed forests, meadows, bog/heathlands sites) and three seasons (spring, summer, autumn) in Sweden. Mites entered traps either by walking or by phoresy, i.e., by being attached to flying insects. We hypothesized (1) that oribatid mite communities in the traps differ between habitats, indicating habitat-limited dispersal, and (2) that oribatid mite communities differ among seasons suggesting that dispersal varies due to changing environmental conditions such as moisture or resource availability. The majority of the collected species were not typically soil-living species but rather from habitats such as trees, lichens and mosses (e.g., Carabodes labyrinthicus, Cymbaeremaeus cymba, Diapterobates humeralis and Phauloppia lucorum ) indicating that walking into the traps or entering them via phoresy are of greater importance for aboveground than for soil-living species. Overall, oribatid mite communities collected in the traps likely originated from the surrounding local habitat suggesting that long distance dispersal of oribatid mites is scarce. Significant differences among seasons indicate higher dispersal during warm and dry periods of the year. Notably, 16 species of oribatid mites collected in our study were sampled for the first time in Sweden. This study also demonstrates that Malaise traps are a meaningful tool to investigate spatial and temporal patterns of oribatid mite communities.

Oil palm and rubber expansion facilitates earthworm invasion in Indonesia - Anton Potapov; Ina Schaefer; Malte Jochum; Rahayu Widyastuti; Nico Eisenhauer; Stefan Scheu (Biological Invasions, 2021)
Deforestation, plantation expansion and other human activities in tropical ecosystems are often associated with biological invasions. These processes have been studied for above-ground organisms, but associated changes below the ground have received little attention. We surveyed rainforest and plantation systems in Jambi province, Sumatra, Indonesia, to investigate effects of land-use change on the diversity and abundance of earthworms—a major group of soil-ecosystem engineers that often is associated with human activities. Density and biomass of earthworms increased 4—30-fold in oil palm and rubber monoculture plantations compared to rainforest. Despite much higher abundance, earthworm communities in plantations were less diverse and dominated by the peregrine morphospecies Pontoscolex corethrurus, often recorded as invasive. Considering the high deforestation rate in Indonesia, invasive earthworms are expected to dominate soil communities across the region in the near future, in lieu of native soil biodiversity. Ecologically-friendly management approaches, increasing structural habitat complexity and plant diversity, may foster beneficial effects of invasive earthworms on plant growth while mitigating negative effects on below-ground biodiversity and the functioning of the native soil animal community.

Invasive lumbricid earthworms in North America—Different life histories but common dispersal? - Andreas Klein; Nico Eisenhauer; Ina Schaefer (Journal of Biogeography, 2020)
Aim Lumbricid earthworms are invasive across northern North America, causing notable changes in forest ecosystems. During their range expansion, they encountered harsher climatic conditions compared to their native ranges in short time (~400 years). This study investigated if (a) dispersal barriers, (b) climatic selection or (c) anthropogenic activities, that is fishing bait disposal, structure the dispersal of free‐living earthworm populations. Location North America, forest habitats along former Wisconsinan glaciation line. Taxon Lumbricus terrestris , L. rubellus . Methods Lumbricus terrestris and L. rubellus co‐occur in the same habitats but differ in ecology and use as fishing bait. Both species were sampled in five transects ranging from the east to the west coast of northern North America, including major dispersal barriers, three different climate zones, and bait shops near sampling locations. Genetic diversity and structure were compared between the two species, and the presence of free‐living bait shop genotypes was assessed using four markers (COI, 16S rDNA, 12S rDNA, and H3). Results Populations of both species were genetically diverse with some geographic structure, which was more pronounced in L. terrestris than in L. rubellus . Common haplotypes were present in all regions, but locally restricted haplotypes also occurred. Furthermore, two distinct genetic clades of L. terrestris co‐occurred only in the two most distant transects (Alberta and Minnesota). Genotypes identical to bait individuals were omnipresent in field populations of L. terrestris . Main Conclusions Genetic diversity was high in both species, and invasive populations represented a genetic subset of European earthworms. Geographic and climatic dispersal barriers affected the less mobile species, L. terrestris , resulting in differences in genetic structure between the two species. Our results indicate common long‐distance dispersal vectors and vectors affecting only L. terrestris . The roles of climate and anthropogenic activities are discussed, providing additional explanations of dispersal and new insights into establishment of invasive earthworm populations.

Cover - Tancredi Caruso; Ina Schaefer; Frank Monson; Aidan M. Keith (Journal of Biogeography, 2019)

Oribatid mites show how climate and latitudinal gradients in organic matter can drive large‐scale biodiversity patterns of soil communities - Tancredi Caruso; Ina Schaefer; Frank Monson; Aidan M. Keith (Journal of Biogeography, 2019)
Aim The factors determining spatial distributions and diversity of terrestrial invertebrates are typically investigated at small scales. Large‐scale studies are lacking for soil animals, which control microbial communities and represent one of the most diverse yet poorly known animal assemblages. Here, we analyzed a major group (Oribatida) to test whether belowground macroecological patterns can be predicted by climatic variables, vegetation and large‐scale variation in key soil properties. Location We modelled the multivariate distribution of more than 100 species using biodiversity data collected across Great Britain in the framework of the Countryside Survey ( http://www.countrysidesurvey.org.uk ). Methods We analyzed species‐level data from 582 samples collected across 162 hectads (10 × 10 km) covering the largest possible range of vegetation types, soil properties and climatic conditions within GB . We created the first large‐scale maps of soil animal diversity metrics at the GB scale, including novel estimates of metrics of phylogenetic diversity (PD). Using structural equation modelling, we quantified the direct and indirect effects of location (latitude, longitude), plant community structure and abiotic factors such as precipitation on species composition, richness and PD. Results We found that variation in species composition follows a latitudinal gradient with diversity generally increasing northward. The latitudinal variation in species composition drives PD via changes in both species richness and phylogenetic distance between species. This gradient is mostly determined by latitudinal variation in precipitation and organic matter, which were very good predictors of species composition. Precipitation and organic matter were, however, relatively weak while statistically significant predictors of diversity metrics. Conclusions Past studies have emphasized the unpredictability of species distributions and variation in species composition in hyper diverse soil animal communities. However, past studies were conducted at small scales, where stochastic factors may weaken the signal of deterministic factors. Oribatid mites in our study show for the first time that the large scale latitudinal gradients in climate and organic matter predict not only variation in species composition but also taxonomic and PD of soil animal communities.

Convergent evolution of aquatic life by sexual and parthenogenetic oribatid mites - Alena Krause; Patrick Pachl; Garvin Schulz; Ricarda Lehmitz; Anna Seniczak; Ina Schaefer; Stefan Scheu; Mark Maraun (Experimental and Applied Acarology, 2016)

Phylogeny and species delineation in European species of the genus Steganacarus (Acari, Oribatida) using mitochondrial and nuclear markers - Victoria Kreipe; Elena Corral-Hernández; Stefan Scheu; Ina Schaefer; Mark Maraun (Experimental and Applied Acarology, 2015)